Effect of process parameters on surface roughness in HPC drilling of AISI 1055 steel / H.V. Shete and M.S. Sohani - H.V., Shete; M.S., Sohani (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2020)
Data regarding the influence of high-pressure coolant on the performance of drilling process using design of experiment has been limitedly available. This paper presents the effect of higher coolant pressures along with spindle speed, feed rate and peck depth on the surface roughness of hole using Taguchi technique. Experimental set up was developed consisting of specially manufactured high-pressure coolant system and high-pressure adapter assembly attached to vertical machining center. Developed experimental set up has optimized utilization of non-through coolant vertical machining center in a small-scale industry. Experiments were conducted on AISI 1055 steel with TiAIN coated drill on the vertical machining center. Taguchi technique was used for design of experiment and analysis of results. Results revealed that the surface roughness improve till coolant pressure reaches to an optimum value of 13.5 bar and there after it decreases. Coolant pressure and spindle speed was the significant process parameters for the hole surface roughness. Surface roughness at the top of hole was considerably lower than the bottom of hole, under the action of all process parameters. Supply of coolant at high pressure has resulted in lower surface roughness even with large peck depth; which indicate that, manufacturing cost can be reduced with the use of high-pressure coolant in drilling.